(untitled) (Research, Society and Development, 2024)
Objective: This study aims to conduct a integrative review on breast cancer, highlighting the associated risk factors and the importance of prevention and early detection. Methods: A integrative review was conducted, selecting information published between 2020 and 2024. The research was conducted in virtual libraries using the descriptors “breast cancer”, “risk factors” and “prevention”. Only texts in Portuguese and English were included. Results: The data analysis revealed three main topics: diagnosis, treatment, and risk factors. Early detection through mammograms and self-examinations is crucial for increasing survival rates. Treatment involves surgical and systemic interventions, with the SUS (Unified Health System) playing a fundamental role in access to oncology care. Identified risk factors include advanced age, inadequate lifestyle habits, and exposure to environmental agents. Conclusion: Early detection and awareness of risk factors are essential in the fight against breast cancer. The SUS should continue to promote educational campaigns and expand access to examinations and treatments, aiming for more favorable outcomes for affected women.